Nutritional quality of four organic fertilizers produced from mixtures of vegetable and cattle residues - Hernández-Rodríguez, Ofelia Adriana (REVISTA TERRA LATINOAMERICANA, 2013)
Use of untreated crop and livestock residues is an important source of water and soil pollutants. Composting mixtures of manure from dairy herds, manure from chicken, sawdust, and corn by-products was evaluated as a technique for producing quality compost for use in agriculture. As quality indicators physicochemical parameters were evaluated: temperature, pH, carbon / nitrogen (C/N) and macro and micronutrients. Observations were made over 24 weeks to describe nutrient dynamics during decomposition and nutritional quality in the final products. Statistical analysis was performed using a completely randomized design with 2 × 2 factorial arrangement: factor A consisted of two types of manure, factor B was represented by plant debris. The experiment was established with five replicates and repeated sampling every six weeks. Tukey (α = 0.05) was used for comparison of means. After 24 weeks a reduction in C/N values in the mixtures was observed in the range of 4.9 to 12.9. Also, the total content of N-NO3 increased. Mixtures of chicken manure with sawdust (T1-GA) and harvest residues (T3-GE) showed the best conditions for the following variables: organic C, 10.9 and 13.4%; N-total, 2.3 and 2.1%; C/N ratio, 4.9 and 6.5; N-NO3, 1190 and 1473 mg k-1; P 0.111 and 0.114%; Cu, 56 and 48 mg k-1; Fe, 1633 and 1662 mg k-1, and Mn, 7.8 and 7.9 mg k-1, respectively. This suggests their potential use for the production of organic fertilizers.